Identification of Misconceptions in Chemical Bonding Materials Using Three Tier Diagnostic Test - Setiawan, Nur Candra Eka; Ilahi, Putri Ridha (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Chemistry learning focuses on understanding concepts, thus students who get difficulty understanding the concepts of chemistry learning will experience conceptual mistakes, especially abstract concepts such as chemical bonds. Students' difficulty understanding the material of chemical bonds can occur due to misconceptions. The misconceptions will hinder the construction and assimilation of new knowledge in students and thus students will experience difficulties in learning chemistry. To address such issue, an instrument for detecting misconceptions in chemistry is necessary to find out the misconceptions that occur among learners. The identification of such emerging misconceptions in understanding the subject matter can be analyzed using a three-tier multiple-choice diagnostic test. The present study was carried out to determine the presence or absence, and the percentage of misconceptions regarding chemical bonding material using the Three Tier Test diagnostic test. Conducted through purposive sampling technique, this research-based paper is a type of qualitative research with a descriptive approach. The research instrument uses a three-tier test objective test. The data obtained was analyzed descriptively for each student's response by using students' level of understanding list. In general, the results obtained in this line of research showed that; (1) Indicator 1, student misconceptions were 91.17% (2) Indicator 2, student misconceptions were 64.14%, (3) Indicator 3, student misconceptions were 67.64%, (4) Indicator 4, student misconceptions were 76.47%. (5) Indicator 5, students' misconceptions were 63.23%. By way of conclusion, the present project argues that there were misconceptions that occured in students of SMA Negeri 1 Class X Teluk Kuantan on the chemical bonding material, with the percentage 72.53% students experiencing misconceptions, 14, 98% students do not understand the concept, and the rest 12.48% students understand the concept of chemical bonding.Keywords: misconception, diagnostic test, three tier test